2017
DOI: 10.1016/j.rasd.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between social communication on the ADOS and real-world reciprocal social communication in children with ASD

Abstract: Background While many children with autism spectrum disorders (ASDs) communicate better with adults than peers, diagnostic measures are given by adult examiners. These measures may not accurately capture the deficits that children with ASD have in communicating with their peers. Method This study examined the ability of the Autism Diagnostic Observation Schedule (ADOS) Social Communication scale to predict reciprocal communication in children with ASD during natural play with peers using the Peer Interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Based on these research findings, researchers can ensure the corresponding brain regions to social cognitive impairment in order to provide efficient treatment. For example, impairment of reciprocal social interactions is regarded as a key sign of individuals with autism spectrum disorder (ASD; Qualls and Corbett, 2017 ). However, the etiology of ASD remains largely unknown.…”
Section: Future Challenges and Directionsmentioning
confidence: 99%
“…Based on these research findings, researchers can ensure the corresponding brain regions to social cognitive impairment in order to provide efficient treatment. For example, impairment of reciprocal social interactions is regarded as a key sign of individuals with autism spectrum disorder (ASD; Qualls and Corbett, 2017 ). However, the etiology of ASD remains largely unknown.…”
Section: Future Challenges and Directionsmentioning
confidence: 99%
“…A few studies have examined the association between intelligence and social communication or motivation. Those studies examined ASD populations and found significant correlation between intelligence and social communication [ 34 36 ]. Qualls et al examined adolescents with ASD and reported positive association between scores of the Social Communication Questionnaire (SCQ; [ 37 ]) and IQ [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Those studies examined ASD populations and found significant correlation between intelligence and social communication [ 34 36 ]. Qualls et al examined adolescents with ASD and reported positive association between scores of the Social Communication Questionnaire (SCQ; [ 37 ]) and IQ [ 34 ]. To assess a general population, one study conducted with more than 5000 participants [ 38 ] revealed that higher verbal IQ has a significant association with better social communication, as measured by Social Communication Disorders Checklist and Children’s Communication Checklist, only in female participants.…”
Section: Introductionmentioning
confidence: 99%
“…Prominently discussed constructs underlying the social challenges for individuals with autism include emotion recognition [ 10 , 11 ], theory of mind [ 12 , 13 ], and executive functioning [ 14 , 15 ]. Other contributing constructs include social motivation [ 16 , 17 ], social reciprocity [ 18 ], and social problem solving [ 19 , 20 ]. Importantly, these constructs are not orthogonal; rather, they appear to be interrelated components to an integrated whole (for brief review, see [ 21 ]).…”
Section: Introductionmentioning
confidence: 99%